Legal mechanisms to combat trade dumping within the framework of the World Trade Organization - Baouche, Dalila (Journal of Human Sciences, 2020)
Anti-dumping is one of the most important instruments for protecting free competition in the international trading system, as an illegal international trade practice that is extremely dangerous to domestic industry. To this end, an entire agreement, called the "Anti-Dumping Agreement", has been drawn up indicating the application of Article 6 of GATT 1994 within the framework of the World Trade Organization . The Convention aims to increase international competition, liberalize foreign trade and open markets among States while giving them the right to protect their national products against unfair and harmful competition as a result of dumping.